Organizational Diagnosis in the Film Industry: Fourth Release of the Marvel Series - Afifah Shalihah; Ratih Purbasari; Margo Purnomo (Soegijapranata Catholic University, 2023)
The use of digital technology in industries brings advantages. The film industry which uses digital media for distribution has succeeded in increasing revenue from exporting films. Marvel Studios collaborate with Disney to make the series available on the Disney Hotstar app. Connoisseurs of the series grew in number and diversity. Of the seven series released, Loki has the highest audience while Ms. Marvel has the lowest audience. The level of audience must be addressed because it affects the income and sustainability of the business in the film industry. Next films must improve the reputations to make regular audiences and newcomers enjoy the products created. Organizational diagnosis is one method for identifying needs, problems, and quick solutions. This article discusses organizational diagnostic method based on system thinking to diagnose a series created by Marvel Studios in the early stages of development using the component model. The sample was negative comment/critique. The results show that the main component has to be improved is the storyline of a recently released series. Emotional engagement gains the smallest point.